The Fire-Raisers: Bentham and Torture - Jeremy Davies (19, 2012)
Jeremy Bentham has frequently been regarded as the father of the ‘ticking bomb’ argument in defence of interrogational torture. The first part of this article draws attention to a transformation in his theory of torture between about 1777 and 1804. His later work anticipates the modern utilitarian case for torture to a striking extent, whereas his earlier writings – although they too defend the practice – are alien to widespread contemporary assumptions. In the second part I argue that those early torture writings have substantial implications for Bentham’s philosophy as a whole. Bentham equivocates as to whether or not physical pain can exert irresistible control over its victim’s will. Intense bodily hurt may become a kind of psychological absolute, one that is perhaps necessary to his thought but is at odds with his principle that all motivations can be traded off against others.(Image: Anon, Jeremy Bentham, oil on canvas. Credit: © UCL Art Museum, University College London)